(untitled) (Revista Contexto & Educação, 2023)
This article presents an excerpt of a dissertation on the development of visual literacy in the process of teacher training in Art. This research sought to verify how the theoretical and methodological approach of this type of literacy is made in undergraduate courses in Visual Arts. In addition, information about the academic and professional profile of art teachers were also raised in an extension course for this audience. In this course, the Grammar Visual Design was presented as a theoretical framework to support the pedagogical practices of image reading and visual literacy and, during it, a case study was carried out. The results show that visual literacy is not privileged in Visual Arts courses and, therefore, its approach is unsatisfactory in Basic Education. Thus, the offer of courses that develop the aforementioned theoretical support can assist in the mediation of teaching practices of visual literacy in this teaching segment.